(untitled) (Sagasteguiana, 2021)
Se actualiza los registros de observaciones en el ámbito de la provincia de Lima para la lagartija Gymnophtalmidae Macropholidus ruthveni, considerada especie introducida en la zona. Palabras clave: Herpetología, Sauria, Gymnophtalmidae, Especie introducida. Abstract The records of observations in the area of ​​the province of Lima are updated for the Gymnophtalmidae Macropholidus ruthveni lizard, considered an introduced species in the area. Keywords: Herpetology, Sauria, Gymnophtalmidae, Introduced species.